AUDIT OF CHILDHOOD DIARRHOEAL MANAGEMENT BY HEALTH PROFESSIONALS IN NORTH EASTERN NIGERIA - ALHAJI MA; MUSTAPHA MG; ASHIR GM; IBRAHIM AB (Kanem Journal of Medical Sciences, 2011)
Background: diarrhea is still an important cause of under 5 morbility and mortality especially in developing countries like Nigeria. Objectives: the management practices of childhood dirrhoea by nurses and midwives in two health institutions in northestern Nigeria were assessed. Method: The study was conducted in the University of Maiduguri Teaching Hospital, Maiduguri and Federal Medical Centre Azare, Nigeria in June 2009 by administering closed ended self administered pre-tested questionnaire. Results: A total of 86 nurses/midwives answered and returned the questionnaire. Of the 86 respondents, 66 were females, while the remaining 20 were males. According to the respondents, bacteria is the commonest cause of childhood diarrhoea followed by teething; 36(41.9%) and 18(20.9), respectively. Seventy seven (89.5%) of the respondents would use ORS first in the treatment of childhood diairhoea. While 12 (14.0%) of the nurses/midwives identified up to three home fluids, apart from the "conventional" ORS/SSS that can be used in the management of childhood diarrhoea, 22 (25.6%) respondents identified no other home fluids. Although, up to 54 (62.8%) of the respondents would increase the feeding frequency of a child with diarrhea, 17(19.8%) of them would stop feeding. At least one correct indication for referral and preventive measures of childhood diarrhoea was fielded by 50 (58.1%) and 73 (84.9%) of the respondents respectively. Conclusion: Although the management practices of childhood diarrhoea among the nurses and midwives was generally satisfactory, some gaps were identified. There is therefore the need for continued training of health workers in the management of common childhood illnesses.